Progress on child safety action in Europe: the results of the 2012 child safety country profiles. (7th October 2012) - Turner, SL; Lyons, RA; Macey, SM; MacKay, M; Vincenten, J
Abstract : Background: Despite injury reductions and safety improvements over the last 30 years, injury remains a leading cause of death and disability for children and adolescents in Europe. As part of the European TACTICS (Tools to Address Childhood Trauma, Injury and Children's Safety) project, Child Safety Country Profiles were developed to measure child injury rates in 36 European countries; enabling European-level comparisons. Aims/Objectives/Purpose: To calculate child injury mortality and morbidity rates for 36 European countries included in the CSAP project. Methods: Child injury data were extracted from the World Health Organization Mortality and Morbidity databases', for all countries excluding England and Wales, where data were provided by the Office for National Statistics and Public Health Wales, respectively. Age standardised injury rates were calculated by gender, age, cause and intent of injury, using the most recent data available. Potential years of life lost (PYLL) and select socio-demographic measures were also identified. Results/Outcomes: Child injury death and disability rates vary greatly between European countries. In 2010, the Netherlands reported the lowest child injury death rate (4.98 per 100 000) and Lithuania reported the highest (23.91 per 100 000); over four times higher than in the Netherlands. Sweden reported the lowest unintentional injury mortality rate (2.73 per 100 000), and Greece the lowest intentional injury mortality rate (0.48/100 000). Significance/Contribution to the field: Results from these analyses, will support the TACTICS project, and will help measure progress towards and setting of targets for the reduction of child and adolescent injury-related death and disability in Europe.